Employee behavior and implementing 5S and total productive maintenance in Kurdish cement factories, Iraq - Hama Kareem, Jamal Ahmed (American Scientific Publishers, 2015)
Maintenance of productive equipment has become increasingly a challenge for many organizations, particularly for organizations in developing countries. The modern and technologically advanced equipment not only provide the effective products in terms of the cost, but they also work on reducing the costs of maintenance. However, the maintenance of these equipments requires specialized techniques to be implemented for their maintenance and up gradation. Many organizations rely modern techniques like 5S and TPM to maintain and acquire the advantage of cost effectiveness. Nevertheless, there are many organizations face problems during the implementing these techniques in the main; this is because these organizations do not take into consideration the most important element, which represent the human resource. Employee behavior and attitude towards modern techniques can either lead to their successful implementation or failure. The present study is an attempt to ascertain the role of employees’ behavior towards implementing 5S and TPM. To achieve this end, the quantitative method for data collection in the framework of the case study was chosen, this has been through the use of a questionnaire survey that has already been tested. The sample of the study was 354 respondents and who were selected based on stratified sampling technique. The criteria for choosing the respondents to be part of the study were based on the full time employee of the plant, and also on the involved in implementation of 5S and TPM. The findings show that motivation and morale, fear of loss of job and increased workload, significantly impact the effective implementation of these techniques (5S and TPM). However, the employees’ awareness and responsibility have had an insignificant impact toward implementation of 5S and TPM. The findings of this study consider important to top management of the organizations. Finally, the study concludes with future directions.